Applied heat exchanger network retrofit for multi-period processes in industry: A hybrid evolutionary algorithm. (May 2022) - Stampfli, Jan A.; Ong, Benjamin H.Y.; Olsen, Donald G.; Wellig, Beat; Hofmann, René
Highlights: Evolutionary algorithm for multi-period heat exchanger network retrofit. Additional constraints are implemented to ensure practical results. Mixer configurations to ensure a flexible network are investigated in detail. Lambert W-function is used for the explicit temperature calculation. Graphical abstract: Abstract: In Swiss process industry, process integration is often applied to retrofit existing plants with multi-period operation. Such periods may experience a high degree of variation in temperature or mass flow. Some process streams may not exist in every period or are soft streams. The resulting retrofitted network needs to be able to ensure feasible heat transfer in each period by the integration of mixer configurations to control the temperature. These attributes increase the complexity of the solution space. Hence, this work proposes an evolutionary two-level algorithm for heat exchanger network retrofit. Genetic algorithm is used for topology optimization and a differential evolution algorithm handles the heat loads. The algorithm is extended with practical constraints such as a maximum number of heat exchangers. Explicit mixer temperature calculations are implemented using the Lambert W-function. The algorithm was successfully applied to an industrial case study, reducing its total annual cost by approximately 66%.